Novel insights into the assembly and function of human nuclear-encoded cytochrome c oxidase subunits 4, 5a, 6a, 7a and 7b - Fornuskova, Daniela; Stiburek, Lukas; Wenchich, Laszlo; Vinsova, Kamila; Hansikova, Hana; Zeman, Jiri (The Biochemical journal, 2010)
Mammalian CcO (cytochrome c oxidase) is a hetero-oligomeric protein complex composed of 13 structural subunits encoded by both the mitochondrial and nuclear genomes. To study the role of nuclear-encoded CcO subunits in the assembly and function of the human complex, we used stable RNA interference of COX4, COX5A and COX6A1, as well as expression of epitope-tagged Cox6a, Cox7a and Cox7b, in HEK (human embryonic kidney)-293 cells. Knockdown of Cox4, Cox5a and Cox6a resulted in reduced CcO activity, diminished affinity of the residual enzyme for oxygen, decreased holoCcO and CcO dimer levels, increased accumulation of CcO subcomplexes and gave rise to an altered pattern of respiratory supercomplexes. An analysis of the patterns of CcO subcomplexes found in both knockdown and overexpressing cells identified a novel CcO assembly intermediate, identified the entry points of three late-assembled subunits and demonstrated directly the essential character as well as the interdependence of the assembly of Cox4 and Cox5a. The ectopic expression of the heart/muscle-specific isoform of the Cox6 subunit (COX6A2) resulted in restoration of both CcO holoenzyme and activity in COX6A1-knockdown cells. This was in sharp contrast with the unaltered levels of COX6A2 mRNA in these cells, suggesting the existence of a fixed expression programme. The normal amount and function of respiratory complex I in all of our CcO-deficient knockdown cell lines suggest that, unlike non-human CcO-deficient models, even relatively small amounts of CcO can maintain the normal biogenesis of this respiratory complex in cultured human cells.
Keywords: podjednotky proteinů; Electron Transport Complex IV; RNA interference; RNA Interference; RNA, Messenger; lidé; respirační komplex IV; buněčné jádro; Cell Nucleus; messenger RNA; Protein Subunits; Humans